PERBANDINGAN TINGKAT DAN RUANG LINGKUP PENGUNGKAPAN PELAPORAN KEUANGAN BASIS INTERNET TERHADAP HARGA SAHAM - Emrinaldi Nur DP; Enny Susilowati (Jurnal Keuangan dan Perbankan, 2015)
Applications of Internet financial reporting (IFR) by companies have reduced the asymmetry of informationand facilitate investor access to corporate information. IFR application is considered a good news that allegedlyable to influence the market by watching the stock price, the value of stocks and abnormal stock returns.The purpose of this study was to observe the practice of IFR influence on stock prices by making comparisonsagainst companies that do not apply to IFR and comparison of the company with defferent degree and scope ofdisclosure. The study was conducted on the companies included in the index compass 100 and tested usingevent study approach and independent sample t-test between two groups of samples. Results of tests performedshowed no difference between the market reaction to the company and which do not apply IFR. There is also adifference in price saha and stock value for the company with the different degree and scope of IFR disclosure,while the abnormal returnnya got no support.